Criminal Justice Considerations for Unsubmitted and Untested Sexual Assault Kits: A Review of the Literature and Suggestions for Moving Forward - Pinchevsky, Gillian M. (Criminal justice policy review, 2018)
One of the latest reforms to the criminal justice response to sexual assault involves changes to the submission and testing of sexual assault kits. Across the United States, thousands of kits have either not been submitted to a laboratory or tested by a laboratory, prompting criticisms that victims of sexual assault have not received justice for the crimes perpetrated against them. Jurisdictions across the country have reevaluated their responses to sexual assault, including their investigations and submission and testing of sexual assault kits. It is critical that future efforts respect the recommendations of jurisdictions that have spearheaded earlier reforms and are guided by victim-centered and trauma-informed principles. This article reviews recent research that has been conducted on changes in processing sexual assault kits, provides examples of different approaches to address unsubmitted and untested kits, and suggests ideas for future research and practice to consider as this area moves forward.